Frequency and patterns of exposure to live poultry and the potential risk of avian influenza transmission to humans in urban Bangladesh - Berry, Isha; Rahman, Mahbubur; Flora, Meerjady Sabrina; Greer, Amy L.; Morris, Shaun K.; Khan, Iqbal Ansary; Sarkar, Sudipta; Naureen, Tanzila; Fisman, David N.; Mangtani, Punam (Scientific reports, 2021)
Avian influenza is endemic in Bangladesh, where greater than 90% of poultry are marketed through live poultry markets (LPMs). We conducted a population-based cross-sectional mobile telephone survey in urban Dhaka, Bangladesh to investigate the frequency and patterns of human exposure to live poultry in LPMs and at home. Among 1047 urban residents surveyed, 74.2% (95% CI 70.9–77.2) reported exposure to live poultry in the past year, with the majority of exposure occurring on a weekly basis. While visiting LPMs was less common amongst females (40.3%, 95% CI 35.0–45.8) than males (58.9%, 95% CI 54.0–63.5), females reported greater poultry exposure through food preparation, including defeathering (13.2%, 95% CI 9.5–17.9) and eviscerating (14.8%, 95% CI 11.2–19.4) (p < 0.001). A large proportion of the urban population is frequently exposed to live poultry in a setting where avian influenza viruses are endemic in LPMs. There is thus not only ample opportunity for spillover of avian influenza infections into humans in Dhaka, Bangladesh, but also greater potential for viral reassortment which could generate novel strains with pandemic potential.